Economic Researcher & Methodology of Scientific research - F. Sultan, Hassan; K. Alizzi, Najah (Journal of Economics and Administrative Sciences, 2020)
The paper contains a theoretical analysis of the interrelation between methodology of economics used by economic researchers and the methodology of scientific research, encouraging readers to think differently about one of the most complicated & controversial subjects. The analysis begins with the determination of propositions that were discussed and explained in the course of the argument. 1- The economic researcher, like a scientific one, goes after the procedures of physical sciences and benefits of the forms of logic. 2- Economics deals with human behavior while the natural sciences deal with the matter. 3-This similarity and variance are reflected well in the nature of laws and generalizations.